Overvaluation of the real exchange rate and the Dutch Disease: the Colombian case. (2013)
In this study, we estimate the impact of the 2004-2012 energy and mining boom on the real effective exchange rate in Colombia and the sectoral composition of its economy. To this end, we introduce the new “extended Dutch Disease” concept, according to which a currency appreciation may not only occur due to traditional “spending” and “relocation” effects but also due to exports and massive inflows of external capital that finances the booming sector. The empirical results indicate that Colombia experienced an overvaluation of its real exchange rate, which in turn negatively affected the competitiveness of its manufacturing and agricultural sector.